Organ biodistribution, clearance, and genotoxicity of orally administered zinc oxide nanoparticles in mice - Li, Ching-Hao; Shen, Chuan-Chou; Cheng, Yu-Wen; Huang, Shih-Hsuan; Wu, Chung-Che; Kao, Chen-Chieh; Liao, Jiunn-Wang; Kang, Jaw-Jou (Nanotoxicology, 2012)
Abstract Understanding tissue biodistribution and clearance of zinc oxide nanoparticles (ZnO-NPs) is necessary for its risk assessment. Both fed and intraperitoneally injected ZnO-NPs (2.5 g/kg) were absorbed into circulation (within 30 min post-dosing), then biodistributed to the liver, spleen, and kidney. Intraperitoneally injected ZnO-NPs remained in serum for 72 h and could more effectively spread to the heart, lung, and testes, whereas the clearance for fed ZnO-NPs in serum began 6 h after oral administration. Compared with zinc oxide microparticles (ZnO-MPs), ZnO-NPs exhibited much higher absorptivity and tissue biodistribution in fed treatment. A greater fraction of fed ZnO-NPs localised in the liver resulted in transient histopathological lesions. However, superoxide generation and cytotoxicity were showed in vitro treatment with ZnO-NPs (above 20 μg/mL). Considering both in vitro and in vivo data, the ZnO-NPs induced acute liver toxicity which was in compliance with its absorption, biodistribution, and clearance.